The Relationship between Education Level and Age with Compliance in Reporting Needlestick Injuries Among Healthcare Workers at Hospital X - Putri, Amilah Eka; Nadia Muthia Hanifah Amrin; Ummu Kamilah; Rendhar Putri Hilintang; A Ferina Herbourina Bonita (Jurnal EduHealth, 2025)
Needlestick injuries are one of the most common occupational accidents among healthcare workers and carry the risk of transmitting bloodborne diseases such as HIV, HBV, and HCV. The reporting rate of these incidents remains low, influenced by various factors including individual characteristics such as education level and age. To determine the relationship between education level and age with compliance in reporting needlestick injury incidents among healthcare workers at Hospital X. This study used an observational analytic design with a cross-sectional approach. The sample consisted of 70 healthcare workers who had experienced or were at risk of experiencing needlestick injuries, selected based on inclusion criteria. Data were collected using a structured questionnaire that had been tested for validity and reliability, then analyzed univariately and bivariately using the Chi-Square test with a significance level of p < 0.05. The majority of respondents held a bachelor's degree (57.1%) and were aged 20–29 years (61.4%). The highest reporting compliance was found in the bachelor's degree group (90%) and the 20–29 age group (81.4%). Chi-Square test results showed a significant relationship between education level and reporting compliance (p = 0.042) and between age and reporting compliance (p = 0.031). The main reason for not reporting was the perception of low infection risk (55.7%). Education level and age are significantly related to compliance in reporting needlestick injuries. Interventions to improve compliance should focus on continuous education, ease of reporting procedures, and strengthening the culture of occupational safety.